Impact of Islamic Cultural Principles on Firm Performance: The Mediating Role of Product Innovation (Al-Qamar, 2026)
The purpose of this study is to investigate the mediating role of product innovation in the relationship between Islamic cultural principles and firm performance. Furthermore, in this study, the researchers have assumed that Hofstede's cultural dimensions, such as power distance, individualism, masculinity, and uncertainty avoidance, are inherent to Islamic culture. A survey was conducted among the managers of 280 small and medium-sized enterprises (SMEs) adopting Islamic culture in Lahore, Pakistan. The proposed hypotheses were tested using structural equation modeling (SEM) via SmartPLS. Moreover, the results indicate that Islamic culture is positively and statistically significantly associated with product innovation and firm performance. However, the cultural aspects of masculinity do not show any significant relationship with innovation outcomes, reflecting the balanced and ethical orientation emphasized in Islamic teachings. Furthermore, product innovation in Pakistan's SME's sector plays a significant mediating role in the relationship between Islamic cultural principles and firm performance. The results indicate that organizations operating in the light of Islamic ethical values can improve performance by promoting innovation in accordance with Islamic principles. Although previous literature has recognized national culture as a determinant of organizational performance, empirical evidence linking Islamic cultural principles with innovation and performance is particularly limited in the Pakistani context. This study provides empirical insights into Islamic management and business research into how innovation mechanisms transform Islamic cultural values into enhanced organizational performance.
Keywords: Power Distance, Masculinity, Individualism, Uncertainty Avoidance, product innovation, firm performance